Long-read assemblies reveal structural diversity in genomes of organelles – an example with Acacia pycnantha - Anna E. Syme; Todd G. B. McLay; Frank Udovicic; David J. Cantrill; Daniel J. Murphy (GigaByte, 2021)
Organelle genomes are typically represented as single, static, circular molecules. However, there is evidence that the chloroplast genome exists in two structural haplotypes and that the mitochondrial genome can display multiple circular, linear or branching forms. We sequenced and assembled chloroplast and mitochondrial genomes of the Golden Wattle, Acacia pycnantha, using long reads, iterative baiting to extract organelle-only reads, and several assembly algorithms to explore genomic structure. Using a de novo assembly approach agnostic to previous hypotheses about structure, we found that different assemblies revealed contrasting arrangements of genomic segments; a hypothesis supported by mapped reads spanning alternate paths.